You can find it in the air (index 6010 again) (Journal of the College of Basic Education, 2022)
Since the beginning of grammatical writing, the authors of this matter have been competing in choosing the most argumentative evidence.And strength, as a scholar in Arabic cannot be in the scientific rank that puts him in the ranks of scholars.His opinion is accepted and his statements cited without having evidence, proofs, and convincing arguments to prove them.The validity of his sayings and opinions, and he corrects his issues alongside others and their doctrines.The indispensable evidences of Arabic scholars, ancient and modern, so the grammarians' attention was directed towards